Physiological responses, growth and productivity of oil palm (Elaeis guineensis Jacq.) as affected by boron fertilization - Prasetiyanto, Lukas Priyo; Putra, Eka Tarwaca Susila; Hanudin, Eko (Faculty of Agriculture, Universitas Gadjah Mada jointly with PISPI, 2024)
Boron (B) is an essential micro nutrient that is needed by oil palms, especially to control productivity. The aim of this research was to determine the optimal dose of B for mature oil palms. The research was conducted at a smallholder oil palm plantation located in Katingan Region, Central Kalimantan Province from January to December 2022. The field experiment was a single factor arranged in a Randomized Complete Block Design (RCBD) with three blocks as replications. The factor tested was the dose of B fertilization, consisting of five doses, namely 0 g. trunk⁻¹. semester⁻¹ (control); 25 g. trunk⁻¹. semester⁻¹; 50 g. trunk⁻¹. semester⁻¹; 75 g. trunk⁻¹. semester⁻¹; and 100 g. trunk⁻¹. semester⁻¹. Observations were done on several variables of micro-weather characteristics at the research site, nutrient and physiological characteristics of leaf, morphological characters and plant growth, and yield and yield components of oil palms. The data obtained were then analyzed with analysis of variance (ANOVA) α=5 %, and data showing significant differences between treatments were tested with an orthogonal polynomial. The results showed that B had positive effects on leaf B, P and K concentration and absorption, leaf chlorophyll content, number of midribs, plant height, leaf area per trunk, leaf area index, crop dry weight, pollen fertility, fruit set, pollen viability, fresh fruit bunch weight (FFB) and FFB productivity. The optimal dose of B to optimize oil palms productivity was 60.24 g. trunk⁻¹. semester⁻¹ with a maximum value of FFB productivity of 6.94 tons. trunk⁻¹. semester⁻¹.